Dialogue au masculin : premier magazine homosexuel d'information. (Paris : Dialogue Presse, 1976)
Fonds Suzan Daniel (FSD)
Periodiciteit: maandelijks
Redactie: 9 rue Nicolas-Flamel, 750004 Paris
Frans
Periodiek